Lung cancer diagnosed following an emergency admission: exploring patient and carer perspectives on delay in seeking help - Caswell, Glenys; Seymour, Jane; Crosby, Vincent; Hussain, Asmah; Manderson, Cathann; Farnan, Sarah; Freer, Sarah; Freemantle, Alison; Littlewood, Fran; Wilcock, Andrew (Springer, 2017)
Purpose